Engineering properties of concrete containing natural zeolite as supplementary cementitious material: Strength, toughness, durability, and hygrothermal performance. (January 2015) - Vejmelková, Eva; Koňáková, Dana; Kulovaná, Tereza; Keppert, Martin; Žumár, Jaromír; Rovnaníková, Pavla; Keršner, Zbyněk; Sedlmajer, Martin; Černý, Robert
Abstract: A complex analysis of engineering properties of concrete containing natural zeolite as supplementary cementitious material in the blended Portland-cement based binder in an amount of up to 60% by mass is presented. The studied parameters include basic physical characteristics, mechanical and fracture–mechanics properties, durability characteristics, and hygric and thermal properties. Experimental results show that 20% zeolite content in the blended binder is the most suitable option. For this cement replacement level the compressive strength, bending strength, effective fracture toughness, effective toughness, and specific fracture energy are only slightly worse than for the reference Portland-cement concrete. The frost resistance, de-icing salt resistance, and chemical resistance to MgCl2, NH4 Cl, Na2 SO4, and HCl are improved. The hygrothermal performance of hardened mixes containing 20% natural zeolite, as assessed using the measured values of water absorption coefficient, water vapor diffusion coefficient, water vapor sorption isotherms, thermal conductivity, and specific heat capacity, is satisfactory.